Analysis of the Needs of Developing Teaching Materials Based on Learning Management System - Tri Yunita (CV Media Inti Teknologi, 2022)
The purpose of this research is to analyze the result of the response to the needs of development of Learning Management System for students. This research is a descriptive research part of R&D research using the ADDIE model. The instruments used are observation sheets, interview sheets, and questionnaire sheets. The subjects consisted of physics teachers and class X students with 96 students and 2 teachers. The instruments used in this study are Likert scale, students and teachers in 3 vocational high schools in Bengkulu City strongly agree and need of LMS-based teaching materials is proven to increase students' independence and learning achievement.